2021
DOI: 10.3390/biom12010006
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of Aromatic Amino Acid Residues around Methionine in Proteins

Abstract: Short-range, non-covalent interactions between amino acid residues determine protein structures and contribute to protein functions in diverse ways. The interactions of the thioether of methionine with the aromatic rings of tyrosine, tryptophan, and/or phenylalanine has long been discussed and such interactions are favorable on the order of 1–3 kcal mol−1. Here, we carry out a new bioinformatics survey of known protein structures where we assay the propensity of three aromatic residues to localize around the [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…The local structures (microenvironments) that house amino acids can substantially influence their reactivity. , Examples include the long-lived Tyr radical in Type II ribonucleotide reductase, , the hydrogen-bonded Tyr residue in photosystem II (Tyr z ), , and the hydrogen-bonded Trp indole in lignin/versatile peroxidases. , Herein, we are concerned with Trp and some examples of redox-active Trp and its microenvironments are shown in Figure . Work from our research group, and from others, has shown that Trp amino acid residues are regularly found near Met in proteins from diverse organisms. There also are examples where the sites of Met–Trp interactions are redox active, with the best known example found in cytochrome c peroxidase. , These observations motivated the production and investigation of the protein models here, where Met is strategically introduced proximal to a redox-active Trp.…”
Section: Introductionmentioning
confidence: 99%
“…The local structures (microenvironments) that house amino acids can substantially influence their reactivity. , Examples include the long-lived Tyr radical in Type II ribonucleotide reductase, , the hydrogen-bonded Tyr residue in photosystem II (Tyr z ), , and the hydrogen-bonded Trp indole in lignin/versatile peroxidases. , Herein, we are concerned with Trp and some examples of redox-active Trp and its microenvironments are shown in Figure . Work from our research group, and from others, has shown that Trp amino acid residues are regularly found near Met in proteins from diverse organisms. There also are examples where the sites of Met–Trp interactions are redox active, with the best known example found in cytochrome c peroxidase. , These observations motivated the production and investigation of the protein models here, where Met is strategically introduced proximal to a redox-active Trp.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, we described interactions where three aromatic groups localized around a single Met. 31 While the incidence of these interactions is lower than the bridging interactions noted above, these Met-aromatic "three-bridges" can be found in all classes of proteins. In particular, we identified several instances of these interactions near the sites of heme enzymes involved in oxygen and peroxide chemistry (e.g., cytochrome c peroxidase, catalase, and prostaglandin H synthase).…”
Section: Methionine-aromatic Motifs: Structures Types and Theorymentioning
confidence: 90%
“…We recently described bioinformatics surveys of Met-sulphur-aromatic (Met(S)-aromatic) interactions. 29–31 In the first, the locations of Met(S)-aromatic interactions were assessed in metalloproteins. 29 That investigation revealed several noteworthy features.…”
Section: Methionine-aromatic Motifs: Structures Types and Theorymentioning
confidence: 99%
“…The highly polarizable sulfur atom of the Met side chain can form with other aromatic side chains stronger interactions than Phe. 70,71 Interestingly, these new mutations do not affect the decrease in forskolin-induced cAMP in a significant manner, thus suggesting they do not block the entrance of the JWH-133 ligand probably due to the higher flexibility of Met relative to Phe. Our experimental results point out that the highly stable aromatic cluster between Phe91 2.61 , Phe94 2.64 , His95 2.65 , and Phe282 7.36 (in the Ala282 7.36 Phe mutation) blocks the entrance of JWH-133 to the orthosteric binding site.…”
Section: Experimental Validation Of the Pathway Of Ligand Entrymentioning
confidence: 98%